Administration of the merit pay systems enhancing work outcomes - Azman Ismail,; Nik Malini Nik Mahdi,; Norazila Mat,; Mohd Helmi Ali,; Nur Alia Atiqah Mohd Ali, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study investigates the relationship between administration of merit pay systems and work outcomes. For data collection purposes, self-administered questionnaires were used on the administrative staff of a Malaysian public research university. The analysis of the Smart PLS path model exhibits three important outcomes: first, the implementation of communication and the assessment of performance are important factors that motivate employees to enhance work satisfaction. Second, the implementation of communication is not an important factor that motivates the employees to enhance organisational commitment. Third, the performance assessment is an important factor that motivates employees to enhance organisational commitment. The results in general, corroborate with previous literature, however, the empirical evidence on the effective communication within the organisation is not an important factor in determining organisational commitment. In addition, this paper provides a clear guidance for managers to administer merit pay system in gaining positive work outcomes. This paper goes on to discussion and implications and is thereafter concluded with conclusion therein.